PENYIMPANAN LIMBAH BAHAN BERBAHAYA DAN BERACUN STUDI KASUS PADA PT. SERASI MITRA MOBIL DI BALIKPAPAN - mulya, widya -; L.M. Zainul; Suhendra, Suhendra (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Hazardous and toxic materials and waste have a negative impact on human safety, human health, environmental protection. More than 26 million types of chemical compounds circulating in the world will cause dangerous substances and toxic substances, while in Indonesia there are almost 5.000 species. According to the Central Statistics Agency of the KALTIM Province, the number of cars is 184.566 units, and a large number of vehicles will certainly also increase the use of oil and oil changes, where used oil is included in the dangerous substances and toxic substances category. For motor vehicle repair shops serving oil changes, it is called a producer of dangerous substances and toxic substances and is required to store dangerous substances and toxic substances. According to data from PT. Serasi Mitra Mobil (June 2019), can produce B3 liquid waste of used oil by 30 liters per month. The research objective is to determine the storage of hazardous and toxic waste case studies at PT. Serasi Mitra Mobil in Balikpapan. This research was conducted by direct observation and in depth interviews related to the storage of hazardous and toxic waste. Based on direct observation and in depth interviews, PT. Serasi Mitra Mobil as a produces of dangerous substances and toxic substances is left to other parties. Dangerous substances and toxic substancesis included in the appropriate pachaging but not labeled and symbol, also not placed in a separate building. The necessary repairs consist of having dangerous substances and toxic substances facilities in the form of buildings, tanks or containers, slime, waste piles, waste impoundment, hazardous and rain protected buildings and rain and sun, having lighting, ventilation, drainage, drainage basins, waste buildings dangerous substances and toxic substances must be adhered to by dangerous substances and toxic substances, having emergency equipment. Keywords: Storage, Waste, Hazardous and Toxic Materials.